2023
DOI: 10.1002/jobm.202300308
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure characterization of different types of chlamydospores in Arthrobotrys flagrans

Bo‐bo Wang,
Feng‐hui Wang,
Yu‐jue Wang
et al.

Abstract: The morphological and structural differences of different types of chlamydospore of Arthrobotrys flagrans, a nematophagous fungus, were studied under light microscope and electron microscope to provide a reference for the biological control of parasitic nematodiasis. In this study, A. flagrans isolate F088 dormant chlamydospore and nondormant chlamydospore were selected as the research objects. The structural differences of these spores were observed by optical microscopy through lactol cotton blue, Trypan blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The chlamydospore is usually spherical, with an inner diameter of 24–32 μm and a wall thickness of 2 μm. Wang et al reported that immature chlamydospore was elliptical with a smooth surface and few tubercles, whereas mature spore was spherical with many tubercles on the surface [2–5]. Chlamydospores were produced from the third day, and they increased with the extension of culture time.…”
Section: Introductionmentioning
confidence: 99%
“…The chlamydospore is usually spherical, with an inner diameter of 24–32 μm and a wall thickness of 2 μm. Wang et al reported that immature chlamydospore was elliptical with a smooth surface and few tubercles, whereas mature spore was spherical with many tubercles on the surface [2–5]. Chlamydospores were produced from the third day, and they increased with the extension of culture time.…”
Section: Introductionmentioning
confidence: 99%